Analysis of Sound Translation of Indonesian Names in The Chinese Newspaper “Indonesian Daily” (Yinni Xingzhou Ribao) - Rosella Hasyim; Pauw Budianto (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2021)
In the process of learning Mandarin, Indonesian names are often found transliterated into Mandarin. In this research, the writer will discuss about Indonesian names which are transliterated into Mandarin. This study will discuss the classification of the translation of the sounds of Indonesian names and the findings in translating the sounds of Indonesian names into Chinese which are presented in the Chinese newspaper "Harian Indonesia". This study used descriptive qualitative method. Qualitative descriptive method is used to describe the rules in translating the sounds of Indonesian names along with their groupings. This research also uses literature review techniquesto collect data. From this study, the results of the analysis regarding the grouping of Indonesian names and the rules in translating the sound of Indonesian names in the Mandarin newspaper "Harian Indonesia" were obtained. With the research that the author did, it is hoped that it can help Indonesian students who study Mandarin in understanding and increasing knowledge of the translation of the sounds of Indonesian names in Mandarin and the classification of the translation of the sounds of Indonesian names.